Improving Vocabulary Mastery of Grade X Students Through Picture Cards at MAN Insan Cendekia Kota Palu - Muspira Muspira; Mawardin M. Said; Moh. Abraham Akbar Eisenring; Mochtar Marhum (MASI Mandiri Edukasi, 2025)
This study addresses the problem of limited vocabulary mastery among grade X students at MAN Insan Cendekia Kota Palu, which hampers their ability to communicate effectively in English. The objective was to determine whether the use of picture cards as a teaching medium could significantly improve students’ vocabulary mastery. The research employed a quantitative approach with a quasi-experimental design involving two groups: an experimental group taught with picture cards and a control group taught with conventional methods. The sample consisted of 46 students, selected randomly and divided equally into experimental and control classes. Data were collected through pre-tests and post-tests, and analysed using a t-test. The findings revealed that the experimental group’s mean score increased from 62.48 in the pre-test to 81.91 in the post-test, while the control group only improved from 58.09 to 65.87. The t-counted value (4.38) exceeded the t-table value (1.681) at the 0.05 significance level, confirming that picture cards had a significant positive effect on vocabulary mastery. Beyond score improvement, students in the experimental class also showed greater participation and motivation during learning activities. These findings suggest that visual media, particularly picture cards, can be effectively integrated into EFL classrooms to foster engagement and enhance vocabulary learning outcomes on a broader scale.